Relationships of the very low birth weight infant microbiome with neurodevelopment at 2 and 4 years of age. Issue 7 (23rd August 2022) - Sarkar, Anujit; Prescott, Stephanie M.; Dutra, Samia; Yoo, Ji Youn; Gordon, Jessica; Shaffer, Emily; McSkimming, Daniel; Groer, Maureen E.
Abstract: Very low birth weight (VLBW) infants (<1500 g) are at risk for poor neurodevelopmental outcomes depending on gestational age (GA), birth weight (BW), and morbidity in early life. The contribution of the gut microbiome is not well understood. Stool samples were collected weekly in the neonatal intensive care unit (NICU) from 24 VLBW infants for 6 weeks after admission and then again at 2 and 4 years of age. The Battelle Development Inventory‐2 Screening Test (BDI‐2 ST) was administered at 2‐ and 4‐year time points. VLBW infants had dysbiotic microbiota in the NICU that progressed for most to an adult‐type microbiota by 4 years of age. The BDI‐2 ST results at age of 2 years triggered referral for further testing in 14 toddlers (70%), and by 4 years of age only seven of these 14 continued to require referral. Both NICU infant stool diversity and particular microbial amplicon sequence variants were associated with BDI‐2 ST subscales, particularly for cognition, adaptive, and communication subscales, when controlled for GA, BW, and antibiotic exposure. Network analysis of the NICU infant stool microbial ecology showed differences in children needing neurodevelopmental referral. The results of this preliminary study indicate that the neonatal gut microbiome plays a role in early cognitive and behavioral neurodevelopment.